2001
DOI: 10.1093/occmed/51.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone use and subjective symptoms. Comparison of symptoms experienced by users of analogue and digital mobile phones

Abstract: In 1995 many people reported symptoms such as headaches, feelings of discomfort, warmth behind/around or on the ear and difficulties concentrating while using mobile phones. The number of complaints was higher for people using the digital (GSM) system, i.e. with pulse modulated fields, than for those using the analogue (NMT) system. Our main hypothesis was that GSM users experience more symptoms than NMT users. An epidemiological investigation was initiated including 6379 GSM users and 5613 NMT 900 users in Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
1
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 14 publications
9
75
1
5
Order By: Relevance
“…was associated with duration of exposure in years (2) . In opposite with our study, Sandstorm et al (2001) (36) and Chia et al …”
Section: Data Management and Analysiscontrasting
confidence: 99%
See 1 more Smart Citation
“…was associated with duration of exposure in years (2) . In opposite with our study, Sandstorm et al (2001) (36) and Chia et al …”
Section: Data Management and Analysiscontrasting
confidence: 99%
“…The absence of significant association of Mph exposure to other complaints among Mph workers may be due to short duration for this new job and the young age of this study workers as the mean age of Mph workers was 27.76±7.03. (2) in Saudi Arabia, while other studies found that, the total duration of Mph use was significantly associated with heat sensation around the face, decrease in cognitive functions and minor effects on sleep (34,36,44) . Also decreased hearing, tinnitus and earache among Mph users were significantly associated with the total Mph use (37,45) .…”
Section: Data Management and Analysismentioning
confidence: 90%
“…In addition to headaches, the users of mobile phones reported fatigue and general discomfort, nausea, impaired thermoregulation [5]. Results of the questionnaire on subjective complaints of the mobile phone users conducted in Sweden, Norway, England, USA, New Zealand, Egypt, Saudi Arabia and Australia have shown that headache was the most frequently observed symptom [4,[6][7][8][9][10][11][12]. A study in Australia showed that headache, including migraine and cluster headache, appeared during or shortly after a call was ended, and often intensified during the day.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors have confirmed a significant relationship between the frequency of headache and the use of a mobile phone [7,13], while others have not confirmed such a relationship [14]. It occurred more frequently when using analog than digital phones [9]. In large, follow-up cohort studies performed in Basel (Switzerland) among mobile and cordless phone users no symptoms (headaches and somatic complaints) or tinnitus were observed [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the interaction between mobile phones and brain functions in humans including their effect on hearing [9][10][11][12][13][14][15][16][17]. Some of the similar recent studies have been highlighted below:…”
Section: Discussionmentioning
confidence: 99%